2014
DOI: 10.1002/rnj.154
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of an Oral Care Protocol on PostStroke Survivors

Abstract: These findings demonstrate the importance of oral care in the poststroke patient with dysphagia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 39 publications
(46 reference statements)
3
29
0
Order By: Relevance
“…Further trials have revealed that having a specific oral care programme where an oral assessment is conducted by nondental professionals, mainly nurses, and a specific plan providing dental assistance to the stroke, reduces the length of NPO (no feeding through the mouth) status and reduces the length of patient stay in the hospital (Talley et al 2015). However, a 10-day pilot study in the Midwest USA to determine the 'effects of a new standardised oral healthcare protocol' where registered nurses assisted twice-a-day brushing and flossing along with lip care showed no statistically significant improvement in swallowing ability and oral intake compared to current procedures in the short term (Chipps et al 2014). Additionally, oral interventions may not reduce the amount of opportunistic pathogens in the oral cavity (Lam et al 2013b).…”
Section: Current Attitudes and Practices Of Nondental Professionals Amentioning
confidence: 98%
See 1 more Smart Citation
“…Further trials have revealed that having a specific oral care programme where an oral assessment is conducted by nondental professionals, mainly nurses, and a specific plan providing dental assistance to the stroke, reduces the length of NPO (no feeding through the mouth) status and reduces the length of patient stay in the hospital (Talley et al 2015). However, a 10-day pilot study in the Midwest USA to determine the 'effects of a new standardised oral healthcare protocol' where registered nurses assisted twice-a-day brushing and flossing along with lip care showed no statistically significant improvement in swallowing ability and oral intake compared to current procedures in the short term (Chipps et al 2014). Additionally, oral interventions may not reduce the amount of opportunistic pathogens in the oral cavity (Lam et al 2013b).…”
Section: Current Attitudes and Practices Of Nondental Professionals Amentioning
confidence: 98%
“…However, there is very limited literature available regarding this concept (Brady et al 2006), with the available trials displaying conflicting results about the importance of nondental professionals in poststroke oral care. While Chipps et al (2014) suggested that an oral care protocol involving nurse-assisted brushing and flossing did not significantly improve oral health outcomes, this was a study conducted over only 10 days and included 51 subjects. The short time period and low sample size mean that the results are not highly conclusive.…”
Section: Papermentioning
confidence: 99%
“…Assessments were done by blinded Registered Dental Hygienist evaluators on Day 1 and Day 4. In prior work, we pilot tested this instrument and revised it to improve interrater reliability (Chipps et al, 2014). The THROAT is a valid and reliable instrument to assess the oral cavity score weighted kappa.95-.97 (Dickinson, Watkins, & Leathley, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, little in the literature addresses oral care of the acutely hospitalized nonventilated ICU patient. Improved oral care in poststroke patients with dysphagia in the acute rehabilitation setting resulted in improvement in oral cavity health, swallowing abilities, and intake of oral fluids (Chipps et al, 2014).…”
Section: Background and Significancementioning
confidence: 99%
See 1 more Smart Citation